PENINGKATAN EKSPOR PISANG INDOESIA KE CHINA TAHUN 2016-2018 - Aidil Syahrizan; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Indonesia is one of the largest fresh banana producing countries in the world, Asia, and the largest exporter to China. Starting from the increasing number of exports in 2016-2018, there was an increase in banana exports to China. It turns out that the demand by China has not been fulfilled by Indonesia. This study discusses why there was an increase in Indonesia's fresh banana exports to China in 2016-2018.This study uses qualitative research methods, with the level of analysis of the nation state. The author uses the Heckscher-Ohlin export theory using a liberalism perspective. The data was obtained from an analysis of books, journals, websites, official reports from the Ministry of Trade, the Ministry of Agriculture, and the Indonesian Central Bureau of Statistics regarding cooperation in the export of fresh bananas between Indonesia and China.The research showed the increase of Indonesia fresh banana exported to China. The increase in consumption of fresh bananas by Chinese citizens resulted in China imports from Indonesia to increase. China's demand for fresh bananas from Indonesia could be fulfilled by applying the concept of Phytosanitary Mitigation, and the Indonesian government application of a Gedor Horti’ s policy for the development of horticultural areas so that Indonesia's fresh banana qualification could comply with the requirments.Keyword: Export, fresh banana, Phytosanitary, Gedor Horti